The ALOHA System. - Kuo, F. F. (Computer communication review.)
THE ALOHA SYSTEM is composed of a related series of contracts and grants from a variety of funding agencies with principal support from ARPA, which deal with two main themes: computer communications (TASK 1), and computer structures (TASK 2).Under computer-communications there is work in (a) Studies on computer communications using radio and satellites, (b) The development of a prototype radio-linked time-sharing network, (c) System studies and planning for a Pacific area computer communications network linking major universities in the U.S., Japan, Australia and other Pacific countries.Under computer structures, we are engaged in research/development in multiprocessor computing structures, computer networks, and geographically distributed computing systems. This work is being undertaken in two phases: 1) the establishment of a research facility and 2) the research work itself. The research facility is centered around the BCC 500 computing system.